Modeling crystallization kinetics for selective laser sintering of polyamide 12 - Soldner, Dominic; Steinmann, Paul; Mergheim, Julia (GAMM-Mitteilungen, 2021)
Selective laser sintering (SLS) of polymers represents a widely used additive manufacturing process, where the part quality depends highly on the present thermal conditions. One distinct feature of SLS is the existence of separate temperature regions for melting and crystallization (solidification) and that the process optimally operates within said regions. Typically a crystallization model, such as the Nakamura model, is used to predict the degree of crystallization as a function of temperature and time. One limitation of this model is the inability to compute negative rates of the crystallization degree during remelting. As we will show in this work, such an extension is necessary, considering the varying temperature fields appearing in SLS. To this end, an extension is proposed and analyzed in detail. Furthermore, a dependency of the temperature and crystallization fields on the size of geometrical features is presente